The phenomenon of sharenting and its risks in the online environment. Experiences from Czech Republic and Spain. (March 2020) - Kopecky, Kamil; Szotkowski, Rene; Aznar-Díaz, Inmaculada; Romero-Rodríguez, José-María
Highlights: Child's right to privacy and protection clashes with the right of parents to share these information with the public. 70–80% of parent in Span and Czech Republic share personal information about their children. 3.5% of parents also admitted that they shared online a photograph of their naked child in neonatal or infant age. Abstract: The possibility for parents to share personal and sensitive information about their children, known as sharenting. This phenomenon is becoming more and more common and in recent years is spreading. The objectives of this paper were to analyse the type of content that parents publish about their children and to compare the sharenting behaviour of Czech and Spanish parents. A quantitative methodology was used in a sample of Czech and Spanish parents (N = 1, 460). As part of the research, we monitored how many respondents are sharing, in what environment, through what services and what types of their children's material they share, and to whom they make it available. Among the results is that a large majority of parents publish photographs of their children on social networks accessible to their contacts, while not taking into account the privacy of the child. Finally, the main implications are discussed and a series of recommendations are collected for parents in order to avoid risks in the life of the minor.